2015
DOI: 10.1177/1465116515588621
|View full text |Cite
|
Sign up to set email alerts
|

Falling in love with(in) Europe: European bi-national love relationships, European identification and transnational solidarity

Abstract: Love is often a key factor in migration decisions. Partner relationships and union formation have also been identified as forming an intrinsic part of intra-European migration. Nevertheless, empirical research into intra-European love migration remains rather scarce. In this paper, we focus on the often neglected but substantial intra-European moves. We analyse the relationship between bi-national couple formation, identification as a European and European transnational solidarity. The analyses are based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…solidarity (Van Mol et al, 2015). Therefore our fi rst analytical interest regards the researchers' experiences of mobility within Europe and their attitudes towards Europe and/or European Union.…”
Section: Mobility Europe and Futurementioning
confidence: 99%
See 1 more Smart Citation
“…solidarity (Van Mol et al, 2015). Therefore our fi rst analytical interest regards the researchers' experiences of mobility within Europe and their attitudes towards Europe and/or European Union.…”
Section: Mobility Europe and Futurementioning
confidence: 99%
“…On the other side, the literature on economic migration, which deals with the social aspects and the consequences of mobility for families and life-projects, mainly focuses on low-skilled migration or TCNs, outlining the push factors triggering mobility (see Van Mol et al, 2015). Only recently, studies addressing "precarity" underlined the complex situation of academic researchers (Murgia and Poggio, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…After all, it has been suggested that people who have routine interaction with individuals from other European countries are 'most likely to come to see themselves as Europeans and involved in a European national project' (Fligstein, 2008: 126). As European bi-national couples are exposed to European 'otherness' on a daily basis, they potentially contribute to the establishment of a European society 'from below' (Van Mol, de Valk, & van Wissen, 2015). Existing research into the links between relationships of individuals of different groups and relationship satisfaction mainly focused on the North American context.…”
Section: Introductionmentioning
confidence: 99%
“…This has been named the "conative" or "utilitarian" element of European identity (Kaina and Karolewski 2013;Nissen 2003). Recent research into this conative component, however, suggests this highest form of identity is rarely attained to at present (Van Mol, de Valk, and van Wissen 2015). Unfortunately, I do not dispose of data with which to measure students' solidarity intentions.…”
Section: Theoretical Expectationsmentioning
confidence: 90%